O Projeto Republicano para a educação no Paraná e o processo de (des)mistificação de Júlia Wanderley - Sousa, Nilvan Laurindo (2013)
The current paper is related to the Masters in Education’s dissertation from UEPG’s Post-Graduate Program, with the theme: Republican Project for Education in Parana and the process of (de) mystification of Julia Wanderley. The overall objective was to analyze Julia Wanderley’s formation and professional work, along with her involvement in the magazine “A Escola”. From this main objective, other specific objectives appeared, which were: to study Julia Wanderley a historical subject, as well as her formation and professional work; foreground the context in which Julia Wanderley was immersed; investigate what was the role of the press in the consolidation of her intellectuality, and, also, analyze the 1905 report, published in 1906 by “A Escola” magazine. The historical period delimited for this research started from 1874, Julia Wanderley’s year of birth, to 1918, the year of her death. Along this paper, one aimed to comprehend in what way Julia Wanderley legitimates herself – or is legitimate as an intellectual; what is the role of the press in this process; the reason she is seen as a role model in Education, by a determined segment; and how her report is presented by Escola magazine, published in 1906. To answer these questions, the following working categories were listed: Ideology, Press and Education. The study was structured and organized from the theoretical ideals of dialectical and historical materialism, seeing that, to understand the republican project for education in Parana, it was necessary to investigate the relationships between the historical, economic, political and social contexts. The research had a documental and bibliographical character, and the methodological procedures used were: mapping of documental sources, newspapers from the studied period, periodical magazines and government reports, located in Parana’s Public Library, House of Memory, Paranaense Museum and Public File. The current research was divided in three chapters: on the first chapter, teacher Julia Wanderley’s formation and work were adressed; on the second chapter, the press and the consolidation of republican ideals in Parana were studied; and, on the third chapter, the thoughts of Julia Wanderley were analyzed, through the report of 1905, broadcasted in the Escola magazine of 1906.